Racial and Ethnic Variations in Preventive Dental Care Utilization among Middle-Aged and Older Americans, 1999–2008 - Wu, Bei; Liang, Jersey; Luo, Huabin; Furter, Robert (Frontiers in Public Health, 2013)
Objective: This study examined recent trends of preventive dental care utilization among Americans aged 50 and above, focusing on variations across racial and ethnic groups including Whites, Blacks, Hispanics, American Indians/Alaska Natives, and Asians. Methods: Self-reported information on oral health behaviors was collected from 644,635 participants in the Behavioral Risk Factor Surveillance System (BRFSS) between 1999 and 2008. Results: Despite a significant upward trend of frequency of dental cleaning from 1999 to 2008 (OR=1.02), in 2008 still only 56 to 77% of any ethnic or racial group reported having had a dental cleaning in the previous 12 months. Relative to Whites, Blacks (OR=.64) were less likely to have a dental cleaning in the previous 12 months. These variations persisted even when SES, health conditions, health behaviors, and number of permanent teeth were controlled. In contrast, Hispanics, Asians, and American Indians/Alaskan Natives did not differ from Whites in dental cleanings. Discussion: This is the first study to provide national estimates of the frequency of dental cleaning and associated trends over time for five major ethnic groups aged 50 and above in the U.S. simultaneously. Our findings suggest that public health programs with an emphasis on educating middle-aged and older minority populations on the benefits of oral health could have a large impact, as there is much room for improvement. Given the importance of oral health and a population that is rapidly becoming older and more diverse, the need for improved dental care utilization is significant.